Evaluation of childhood malignancies presenting with musculoskeletal manifestations from two different divisions: a multicenter study - Çağlayan, Şengül; Koç, Begüm Şirin; Baba, Özge; Bağlan, Esra; Kurucu, Burçak; Gezgin Yıldırım, Deniz; Canbolat Ayhan, Aylin; Çakan, Mustafa; Otar Yener, Gülçin; Öztürk, Kübra; Çakmak, Figen; Sönmez, Hafize Emine; et al. (The Turkish Journal of Pediatrics, 2024)
Background. The aim of the study was to evaluate the approaches of pediatric rheumatologists and pediatric hematologists to patients with similar musculoskeletal (MSK) complaints and to highlight the differences that general pediatricians should consider when referring patients to these specialties.Methods. This is a cross-sectional study involving the patients who applied to pediatric rheumatology centers with MSK complaints and were diagnosed with malignancy, as well as patients who were followed up in pediatric hematology centers with a malignancy diagnosis, and had MSK complaints at the time of admission.Results. A total of 142 patients were enrolled in the study. Of these patients, 83 (58.4%) applied to pediatric rheumatology centers, and 59 (41.6%) applied to pediatric hematology centers. Acute lymphoblastic leukemia (ALL) was the most common diagnosis among the patients who applied to both centers, with 80 cases (56.3%). The median age of diagnosis was 87 (interquartile range, IQR: 48-140) months. The most common preliminary diagnosis in pediatric rheumatology centers was juvenile idiopathic arthritis (JIA), with 37 cases (44.5%). MSK involvement was mainly seen as arthralgia, and bone pain. While arthralgia (92.7%) was the most common complaint in rheumatology centers, bone pain (88.1%) was more common in hematology centers. The most frequently involved joints were the knee (62.9%), ankle (25.9%), hip (25%), and wrist (14%). The most common laboratory abnormalities were high lactate dehydrogenase (LDH), high C-reactive protein (CRP), anemia, and high erythrocyte sedimentation rate (ESR). Thrombocytopenia, neutropenia, and high LDH were statistically significantly more frequent in patients admitted to hematology centers than in patients admitted to rheumatology centers (p
Keywords: musculoskeletal complaints; malignancy; pediatric rheumatology; pediatric hematology